Functional silicon dioxide toughened and modified nylon 6 composite fiber and preparation method thereof

Through the modification of nano -nanoxide and mixing with the nylon 6, the nylon 6 composite fiber that is touched by functional silicon dioxide is prepared to solve the problem of lack of traditional nylon 6 fiber properties, significantly improved the pull of the material for pulling the material. Stretching, impact strength and toughness.

CN119372800AInactive Publication Date: 2025-01-28WUHAN QISHENMING TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411795230.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The tensile and impact strength of traditional nylon 6 fibers have poor comprehensive performance, making it difficult to meet the needs of high-performance fibers.

Method used

By modified nano -silicon dioxide, including carboxyl, epoxy, and polyethylene alcohol modification to form functional silicon dioxide, and mix with nylon 6, prepare tougher and modified by melting spinning legal system. Nylon 6 composite fiber.

Benefits of technology

Effectively improve the stretch strength, impact strength and toughness of the nylon 6 composite fiber, improve the dispersability of nano -silica, reduce the phenomenon of gathering, thereby improving the comprehensive performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372800A_ABST
    Figure CN119372800A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fibers, and discloses a preparation method of functional silicon dioxide toughened and modified nylon 6 composite fibers, carboxylated silicon dioxide reacts with ethylene glycol diglycidyl ether to obtain epoxidized silicon dioxide, the epoxidized silicon dioxide reacts with polyvinyl alcohol to obtain polyvinyl alcohol modified silicon dioxide, and the polyvinyl alcohol modified silicon dioxide is blended with nylon 6 to obtain the functional silicon dioxide toughened and modified nylon 6 composite fibers. Hydroxyl groups of polyvinyl alcohol and amide of nylon 6 can form hydrogen bonds, so that the polyvinyl alcohol and the nylon 6 have good compatibility, dispersion of nano silicon dioxide is promoted, and the functional silicon dioxide toughened and modified nylon 6 composite fiber is obtained. The nano silicon dioxide and polyvinyl alcohol molecular chain can improve the tensile strength and other mechanical properties of the composite nylon 6 fiber, so that the application range of the nylon 6 fiber is further expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fibers, in particular to a functional silica toughened modified nylon 6 composite fiber and a preparation method thereof. Background Art

[0002] As material life becomes increasingly abundant, people have higher and higher requirements for fiber fabrics. Among the many fiber matrices, nylon 6 fiber has many advantages such as wear resistance, light weight, and good elasticity, so it is widely used. However, with the rapid development of high-performance fibers in recent years, people have put forward higher requirements on the various properties of nylon 6 fiber. The comprehensive properties of traditional nylon 6 fiber such as tensile strength and impact strength gradually cannot meet people's needs. It is precisely because of this that the application and development of nylon fiber has been greatly restricted. Therefore, the preparation of high-performance nylon 6 composite fibers has attracted more and more attention from academia and industry. Using inorganic nanomaterials as fillers and modifiers to enhance the toughness, strength and other comprehensive properties of nylon 6 matrix has received widespread attention in recent years and has gradually become an important means of modifying nylon 6.

[0003] Nano-silicon dioxide is an inorganic nano-material with excellent performance. In recent years, it has gradually been used as a filler modifier for organic polymer materials. By combining the advantageous properties of silicon dioxide, the comprehensive properties of organic polymer materials such as tensile strength, flame retardancy, and impact resistance are enhanced. Chinese patents such as CN106750271A disclose a method for preparing a nano-silicon dioxide reinforced nylon 6 composite material. By combining the properties of nano-silicon dioxide, a composite material with excellent performance is prepared. However, most of these patents do not modify the nano-silicon dioxide, ignoring the problem of poor dispersibility of nano-silicon dioxide, resulting in the phenomenon that nano-silicon dioxide is easy to agglomerate in the matrix, which makes the modification effect unsatisfactory. Therefore, it is necessary to modify the nano-silicon dioxide to improve its dispersibility while enhancing its functionality so as to further apply it to the modification of organic polymer materials. Summary of the invention

[0004] 1. Technical issues to be resolved In view of the shortcomings of the prior art, the present invention provides a functional silica toughened modified nylon 6 composite fiber and a preparation method, which solves the problem of poor mechanical properties such as tensile strength of nylon 6 fiber.

[0005] (II) Technical solution To achieve the above object, the present invention provides the following technical solution: a functional silica toughened modified nylon 6 composite fiber, the preparation method of which comprises the following steps: (1) Add acetonitrile solvent, nano-silica and succinic acid in a mass ratio of 400-850:10:18-40 into a reactor, mix well, stir and react in an oil bath at 70-90° C. for 12-36 hours, centrifuge, wash and dry after the reaction to obtain carboxylated silica; (2) adding ethanol solvent and carboxylated silica to the reactor, dispersing them evenly with ultrasound, adding ethylene glycol diglycidyl ether and a catalyst, mixing them evenly, transferring them to an oil bath, raising the temperature to react, centrifuging after the reaction, washing and drying to obtain epoxidized silica; (3) Add dimethyl sulfoxide solvent and epoxidized silica to the reactor, and after ultrasonic dispersion for 20-40 minutes, continue to add polyvinyl alcohol and catalyst, transfer to an oil pan, increase the temperature to 60-80°C, stir until completely dissolved, react for 4-12 hours, and after the reaction is completed, filter, wash and dry to obtain polyvinyl alcohol-modified silica; (4) Add nylon 6, polyvinyl alcohol modified silica and 0.6-1.5% of antioxidant 168 into a high-speed mixer, mix well and transfer to a twin-screw extruder for granulation, transfer the masterbatch to a melt spinning machine, set the heating barrel temperature to 110-130°C, and spin to obtain functional silica-reinforced modified nylon 6 composite fibers.

[0006] Preferably, in step (2), the mass ratio of ethanol solvent, carboxylated silica, ethylene glycol diglycidyl ether and catalyst is 300-650:10:2.4-6:0.06-0.2.

[0007] Preferably, the catalyst in step (2) is N,N-dimethylbenzylamine.

[0008] Preferably, the reaction temperature in step (2) is 100-120° C. and the reaction time is 12-24 h.

[0009] Preferably, in step (3), the mass ratio of dimethyl sulfoxide solvent, epoxidized silica, polyvinyl alcohol and catalyst is 450-1200:10:12-25:1-3.5.

[0010] Preferably, the catalyst in step (3) is potassium hydroxide.

[0011] Preferably, in step (4), the mass ratio of nylon 6 to polyvinyl alcohol-modified silica is 100:1.2-4.5.

[0012] 3. Beneficial technical effects Compared with the prior art, the present invention has the following beneficial technical effects: The functional silica toughened modified nylon 6 composite fiber has abundant hydroxyl groups on the surface of nano silica, which can undergo esterification reaction with the carboxyl group at one end of a succinic acid molecule to obtain carboxylated silica. Under the catalytic action of N,N-dimethylbenzylamine as a catalyst, the carboxyl group in the carboxylated silica structure can undergo a ring-opening reaction with the epoxy group at one end of an ethylene glycol diglycidyl ether molecule to obtain epoxidized silica. Under the action of potassium hydroxide as a catalyst, the epoxidized silica can undergo a ring-opening reaction with the hydroxyl group in a polyvinyl alcohol molecular chain to obtain polyvinyl alcohol modified silica, thereby covalently grafting polyvinyl alcohol macromolecules on the surface of the nano silica in a chemical bond connection manner, effectively enriching the functionality of the nano silica, and facilitating its further application in the modification of organic polymer materials.

[0013] The functional silica toughened modified nylon 6 composite fiber is prepared by blending nylon 6, polyvinyl alcohol modified silica and various additives, and then preparing the fiber by melt spinning, so as to finally obtain the functional silica toughened modified nylon 6 composite fiber. The polyvinyl alcohol molecular chain contains a large number of hydroxyl groups that are not involved in the reaction, which can react with the amide group of nylon 6 to form a strong hydrogen bond, so that they have good compatibility with each other, thereby promoting the dispersion of nano silica in the nylon 6 matrix, and improving the agglomeration phenomenon of nano silica to a certain extent. When the composite fiber is subjected to external force, the cracks generated by the stress will be hindered by the nano silica during the extension, forcing the extension of the cracks to be deflected. At the same time, the nano silica can absorb the external stress and transfer the stress to the polyvinyl alcohol molecular chain, so as to effectively enhance the tensile strength and impact strength and other properties of the composite nylon 6 fiber. In addition, the polyvinyl alcohol molecular chain grafted on the surface of the nano silica has high flexibility, which can improve the flexibility of the composite nylon 6 fiber, so as to further enhance the toughness of the composite fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the reaction of carboxylated silica and ethylene glycol diglycidyl ether.

[0015] Figure 2 Schematic diagram of the reaction of epoxidized silica and polyvinyl alcohol.

[0016] Figure 3 It is a graph of tensile strength and elongation at break of composite fibers.

[0017] Figure 4 This is a composite fiber impact strength test chart. DETAILED DESCRIPTION

[0018] To achieve the above object, the present invention provides the following specific implementation methods and examples: A functional silica toughened modified nylon 6 composite fiber, the preparation method comprising the following steps: To achieve the above object, the present invention provides the following technical solution: a functional silica toughened modified nylon 6 composite fiber, the preparation method of which comprises the following steps: (1) Add acetonitrile solvent, nano-silica and succinic acid in a mass ratio of 400-850:10:18-40 into a reactor, mix well, stir and react in an oil bath at 70-90° C. for 12-36 hours, centrifuge, wash and dry after the reaction to obtain carboxylated silica; (2) Add ethanol solvent and carboxylated silica to the reactor, disperse them uniformly by ultrasonication, continue to add ethylene glycol diglycidyl ether and N,N-dimethylbenzylamine, wherein the mass ratio of ethanol solvent, carboxylated silica, ethylene glycol diglycidyl ether and N,N-dimethylbenzylamine is 300-650:10:2.4-6:0.06-0.2, mix them uniformly and transfer them to an oil bath, raise the temperature to 100-120°C, react for 12-24 hours, centrifuge after the reaction, wash and dry to obtain epoxidized silica; (3) Add dimethyl sulfoxide solvent and epoxidized silica to the reactor, and after ultrasonic dispersion for 20-40 minutes, continue to add polyvinyl alcohol and potassium hydroxide, wherein the mass ratio of dimethyl sulfoxide solvent, epoxidized silica, polyvinyl alcohol and potassium hydroxide is 450-1200:10:12-25:1-3.5, transfer to an oil pan, increase the temperature to 60-80°C, stir until completely dissolved, react for 4-12 hours, and after the reaction is completed, filter, wash and dry to obtain polyvinyl alcohol modified silica; (4) Add nylon 6, polyvinyl alcohol modified silica and 0.6-1.5% antioxidant 168 in a mass ratio of 100:1.2-4.5 into a high-speed mixer, mix well and transfer to a twin-screw extruder for granulation, transfer the masterbatch to a melt spinning machine, set the heating barrel temperature to 110-130°C, and spin to obtain functional silica-reinforced modified nylon 6 composite fibers. Example 1

[0019] (1) Add 260 mL of acetonitrile solvent, 5 g of nano-silica and 9 g of succinic acid into a reactor, mix well and stir in an oil bath at 70 ° C for 12 h. After the reaction, centrifuge, wash and dry to obtain carboxylated silica; (2) Add 200 mL of ethanol solvent and 5 g of carboxylated silica to the reactor, disperse evenly by ultrasonication, continue to add 1.2 g of ethylene glycol diglycidyl ether and 0.03 g of N,N-dimethylbenzylamine, mix evenly and transfer to an oil bath, raise the temperature to 100 ° C, react for 12 h, centrifuge after the reaction, wash and dry to obtain epoxidized silica; (3) Add 210 mL of dimethyl sulfoxide solvent and 5 g of epoxidized silica to the reactor, and after ultrasonic dispersion for 20 min, continue to add 6 g of polyvinyl alcohol and 0.5 g of potassium hydroxide, transfer to an oil pan, increase the temperature to 60 ° C, stir until completely dissolved, react for 4 h, and after the reaction is completed, filter, wash and dry to obtain polyvinyl alcohol-modified silica; (4) Add 50 g of nylon 6, 0.6 g of polyvinyl alcohol-modified silica and 0.3 g of antioxidant 168 into a high-speed mixer, mix well and transfer to a twin-screw extruder for granulation, transfer the masterbatch to a melt spinning machine, set the heating barrel temperature to 110 °C, and spin to obtain functional silica-reinforced modified nylon 6 composite fibers. Example 2

[0020] (1) Add 320 mL of acetonitrile solvent, 5 g of nano-silica and 12.5 g of succinic acid into a reactor, mix well and stir in an oil bath at 75 ° C for 16 h. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated silica; (2) Add 260 mL of ethanol solvent and 5 g of carboxylated silica to the reactor, disperse evenly by ultrasonication, continue to add 1.8 g of ethylene glycol diglycidyl ether and 0.05 g of N,N-dimethylbenzylamine, mix evenly and transfer to an oil bath, raise the temperature to 105 ° C, react for 15 h, centrifuge after the reaction, wash and dry to obtain epoxidized silica; (3) Add 300 mL of dimethyl sulfoxide solvent and 5 g of epoxidized silica to the reactor, and after ultrasonic dispersion for 25 min, continue to add 7.5 g of polyvinyl alcohol and 0.8 g of potassium hydroxide, transfer to an oil pan, increase the temperature to 65 ° C, stir until completely dissolved, react for 6 h, and after the reaction is completed, filter, wash and dry to obtain polyvinyl alcohol-modified silica; (4) Add 50 g of nylon 6, 1 g of polyvinyl alcohol-modified silica and 0.4 g of antioxidant 168 into a high-speed mixer, mix well and transfer to a twin-screw extruder for granulation, transfer the masterbatch to a melt spinning machine, set the heating barrel temperature to 115 °C, and spin to obtain functional silica-reinforced modified nylon 6 composite fibers. Example 3

[0021] (1) Add 400 mL of acetonitrile solvent, 5 g of nano-silica and 15 g of succinic acid into a reactor, mix well and stir in an oil bath at 80 ° C for 18 h. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated silica; (2) Add 300 mL of ethanol solvent and 5 g of carboxylated silica to the reactor, disperse evenly by ultrasonication, continue to add 2.2 g of ethylene glycol diglycidyl ether and 0.07 g of N,N-dimethylbenzylamine, mix evenly and transfer to an oil bath, raise the temperature to 110°C, react for 16 h, centrifuge after the reaction, wash and dry to obtain epoxidized silica; (3) Add 380 mL of dimethyl sulfoxide solvent and 5 g of epoxidized silica to the reactor, and after ultrasonic dispersion for 30 min, continue to add 9 g of polyvinyl alcohol and 1.1 g of potassium hydroxide, transfer to an oil pan, raise the temperature to 70 ° C, stir until completely dissolved, react for 8 h, and after the reaction is completed, filter, wash and dry to obtain polyvinyl alcohol-modified silica; (4) Add 50 g of nylon 6, 1.4 g of polyvinyl alcohol-modified silica and 0.5 g of antioxidant 168 into a high-speed mixer, mix well and transfer to a twin-screw extruder for granulation, transfer the masterbatch to a melt spinning machine, set the heating barrel temperature to 120 °C, and spin to obtain functional silica-reinforced modified nylon 6 composite fibers. Example 4

[0022] (1) Add 460 mL of acetonitrile solvent, 5 g of nano-silica and 17.5 g of succinic acid into a reactor, mix well and stir in an oil bath at 85 ° C for 24 h. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated silica; (2) Add 360 mL of ethanol solvent and 5 g of carboxylated silica to the reactor, disperse evenly by ultrasonication, continue to add 2.6 g of ethylene glycol diglycidyl ether and 0.08 g of N,N-dimethylbenzylamine, mix evenly and transfer to an oil bath, raise the temperature to 115°C, react for 18 hours, centrifuge after the reaction, wash and dry to obtain epoxidized silica; (3) Add 460 mL of dimethyl sulfoxide solvent and 5 g of epoxidized silica to the reactor, and after ultrasonic dispersion for 35 min, continue to add 10.5 g of polyvinyl alcohol and 1.4 g of potassium hydroxide, transfer to an oil pan, increase the temperature to 75 ° C, stir until completely dissolved, react for 9 h, and after the reaction is completed, filter, wash and dry to obtain polyvinyl alcohol-modified silica; (4) Add 50 g of nylon 6, 1.8 g of polyvinyl alcohol-modified silica and 0.6 g of antioxidant 168 into a high-speed mixer, mix well and transfer to a twin-screw extruder for granulation, transfer the masterbatch to a melt spinning machine, set the heating barrel temperature to 125 °C, and spin to obtain functional silica-reinforced modified nylon 6 composite fibers. Example 5

[0023] (1) Add 540 mL of acetonitrile solvent, 5 g of nano-silica and 20 g of succinic acid into a reactor, mix well and stir in an oil bath at 90 ° C for 36 hours. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated silica; (2) Add 410 mL of ethanol solvent and 5 g of carboxylated silica to the reactor, disperse evenly by ultrasonication, continue to add 3 g of ethylene glycol diglycidyl ether and 0.1 g of N,N-dimethylbenzylamine, mix evenly and transfer to an oil bath, raise the temperature to 120°C, react for 24 hours, centrifuge after the reaction, wash and dry to obtain epoxidized silica; (3) Add 540 mL of dimethyl sulfoxide solvent and 5 g of epoxidized silica to the reactor, and after ultrasonic dispersion for 40 min, continue to add 12.5 g of polyvinyl alcohol and 1.75 g of potassium hydroxide, transfer to an oil pan, increase the temperature to 80 ° C, stir until completely dissolved, react for 12 h, and after the reaction is completed, filter, wash and dry to obtain polyvinyl alcohol-modified silica; (4) Add 50 g of nylon 6, 2.25 g of polyvinyl alcohol-modified silica and 0.75 g of antioxidant 168 into a high-speed mixer, mix well and transfer to a twin-screw extruder for granulation, transfer the masterbatch to a melt spinning machine, set the heating barrel temperature to 130 °C, and spin to obtain functional silica-reinforced modified nylon 6 composite fibers.

[0024] Comparative Example 1 (1) Add 280 mL of acetonitrile solvent, 5 g of nano-silica and 10 g of succinic acid into a reactor, mix well and stir in an oil bath at 75 ° C for 14 h. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated silica; (2) Add 50 g of nylon 6, 0.8 g of carboxylated silica and 0.4 g of antioxidant 168 into a high-speed mixer, mix well and transfer to a twin-screw extruder for granulation. Transfer the masterbatch to a melt spinning machine, set the heating barrel temperature to 120 °C, and spin to obtain silica-modified nylon 6 composite fibers.

[0025] The composite fibers in the examples and comparative examples were woven into fiber membranes with a size of 3 cm×3 cm, and the tensile strength and elongation at break were tested using a HT-101PT-05 tensile strength tester.

[0026] The composite fibers in the examples and comparative examples were woven into fiber membranes with a size of 3 cm×3 cm, and the impact strength thereof was tested using a DR-802 impact strength tester.

Claims

1. A method for preparing a functional silica toughened modified nylon 6 composite fiber, characterized in that: The following steps are involved: (1) Evenly mix acetonitrile solvent, nano-silica and succinic acid in a mass ratio of 400-850:10:18-40, stir and react in an oil bath at 70-90° C. for 12-36 hours, centrifuge after the reaction, wash and dry to obtain carboxylated silica; (2) adding carboxylated silica to an ethanol solvent, dispersing it evenly with ultrasound, adding ethylene glycol diglycidyl ether and a catalyst, mixing evenly, transferring to an oil bath, raising the temperature to react, centrifuging after the reaction, washing and drying to obtain epoxidized silica; (3) Add epoxidized silica to dimethyl sulfoxide solvent, ultrasonically disperse for 20-40 minutes, then continue to add polyvinyl alcohol and catalyst, transfer to an oil pan, raise the temperature to 60-80°C, stir until completely dissolved, react for 4-12 hours, and after the reaction is completed, filter, wash and dry to obtain polyvinyl alcohol-modified silica; (4) Add nylon 6, polyvinyl alcohol modified silica and 0.6-1.5% of antioxidant 168 into a high-speed mixer, mix well and transfer to a twin-screw extruder for granulation, transfer the masterbatch to a melt spinning machine, set the heating barrel temperature to 110-130°C, and spin to obtain functional silica-reinforced modified nylon 6 composite fibers.

2. The method for preparing a functional silica toughened modified nylon 6 composite fiber according to claim 1, characterized in that: In the step (2), the mass ratio of the ethanol solvent, carboxylated silica, ethylene glycol diglycidyl ether and the catalyst is 300-650:10:2.4-6:0.06-0.

2.

3. The method for preparing a functional silica toughened modified nylon 6 composite fiber according to claim 1, characterized in that: The catalyst in step (2) is N,N-dimethylbenzylamine.

4. The method for preparing a functional silica toughened modified nylon 6 composite fiber according to claim 1, characterized in that: The reaction temperature in step (2) is 100-120° C. and the reaction time is 12-24 hours.

5. The method for preparing a functional silica toughened modified nylon 6 composite fiber according to claim 1, characterized in that: In the step (3), the mass ratio of dimethyl sulfoxide solvent, epoxidized silica, polyvinyl alcohol and catalyst is 450-1200:10:12-25:1-3.

5.

6. The method for preparing a functional silica toughened modified nylon 6 composite fiber according to claim 1, characterized in that: The catalyst in step (3) is potassium hydroxide.

7. The method for preparing a functional silica toughened modified nylon 6 composite fiber according to claim 1, characterized in that: In the step (4), the mass ratio of nylon 6 to polyvinyl alcohol modified silica is 100:1.2-4.5.

Citation Information

Patent Citations

  • Preparation method of nano silicon dioxide reinforced nylon 6 composite

    CN106750271A